Gender Justice in Workplace Sexual Harassment Law Enforcement - Alya Miladina Fatima Baranyanan; Mufti Khakim (Jurnal Cakrawala Hukum, 2026)
Abstract: Women in the workplace remain vulnerable to sexual harassment, whether physical, verbal, or psychological, which impacts their well-being, psychological well-being, and careers. Although Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS) provides a legal framework for protection, its implementation has not been fully effective due to power relations, patriarchal culture, and low legal awareness at both the company and employee levels. This study aims to analyze the implementation of gender justice principles in law enforcement against sexual harassment in the workplace. The study uses empirical normative legal research, combining analysis of legal materials with data from field practices. The approach uses the Statute Approach and the Socio-Legal Approach. Data sources consist of primary data obtained through interviews with Legal Aid Institutions (LBH) and victim support organizations, as well as secondary data covering primary, secondary, and tertiary legal materials. The data analysis method uses normative qualitative analysis by systematically reviewing and interpreting legal and empirical data.